2006
DOI: 10.1007/s00521-006-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Empirical comparisons of feed-forward connectionist and conventional regression models for prediction of first lactation 305-day milk yield in Karan Fries dairy cows

Abstract: In this paper, two connectionist models are proposed based on different learning paradigms, viz., back propagation neural networks (BPNN) and radial basis function neural networks (RBFNN) to predict the first lactation 305-day milk yield (FLMY305) in Karan Fries (KF) dairy cattle. Also, a conventional multiple linear regression (MLR) model is developed for the prediction. In this study, all the models have been developed using a scientifically determined optimum dataset of representative breeding traits of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The analysis of lifetime milk yield (LTMY) is important for various reasons. It is helpful to select genetically superior bulls 4,5 . Milk yield prediction also helps in the selection of animals, which leads to optimal breeding strategies and increased annual genetic progress 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of lifetime milk yield (LTMY) is important for various reasons. It is helpful to select genetically superior bulls 4,5 . Milk yield prediction also helps in the selection of animals, which leads to optimal breeding strategies and increased annual genetic progress 6 .…”
mentioning
confidence: 99%
“…Few studies focus on the capability of ANN to predict LTMY, first lactation 305-day milk yield (FL305DMY), fat and protein concentration of milk, etc. [4][5][6]8,[16][17][18][19] . Some studies showed that prediction of milk yield by using ANN model was more accurate than Wood's model 16,20 as well as by the MLR method [17][18][19]21 .…”
mentioning
confidence: 99%
“…In the species like cattle, in which the generation interval is approx. 5 years, every method that can contribute to the milk yield prediction in cows before the completion of lactation will speed up the process of bull identification and increase genetic progress [46]. In the cited work [47], the input variables in the neural models were the evaluation results from the first four test-day milkings, mean milk yield of a barn, lactation length, calving month, lactation number, proportion of Holstein-Friesian genes in animal genotype.…”
Section: Regression Tasks -Milk Yield Prediction In Cattlementioning
confidence: 99%
“…ANN approach needs specified algorithm to be transformed by a computer program (Grzesiak et al, 2003). The application of ANN in animal sciences and especially in animal breeding data is scanty (Grzesiak et al, 2003;Sharma et al, 2006;Hosseinia, 2007). Therefore, the present investigation was undertaken to predict lifetime milk production on the basis of first lactation traits by MRA and ANN approach and to compare their effectiveness for prediction of lifetime milk production in Sahiwal cattle.…”
Section: Introductionmentioning
confidence: 99%